SISTEM PENDUKUNG KEPUTUSAN PENILAIAN KINERJA TENAGA PENDIDIK DENGAN METODE PROFILE MATCHING - Yuwanda Yuwanda; Dicky Apdillah (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: The performance assessment of educators is an evaluation conducted through observation and monitoring of each main task of educators in the context of career development, rank, and position. The performance assessment of educators includes their ability to master knowledge, skills, and professional attitudes as educators. To determine the quality of the human resources of educators, one of the efforts that can be made is by conducting performance evaluations. As an educational institution, the quality of human resources it possesses greatly impacts the quality of its students. The purpose of this research is to analyze a decision support system using the profile matching method in the performance assessment of educators. The data input into the system includes the alignment of lesson implementation with the lesson schedule, punctuality, mastery of the material, and other aspects related to teaching. From the results of the system testing conducted, the scores obtained were as follows: Supriyati, S.Pd (4.25) with a very suitable predicate, Siti Malihatun Nikmah, S.PD (3.70) with a suitable predicate, Kusmini, S.Pd (3.60) with a suitable predicate, Singgih Peranowo, S.Pd (3.20) with a suitable predicate, Nursamsyiah, S.Pd (3.10) with a suitable predicate, Sunarso, S.Sn (2.90) with an unsuitable predicate. Based on these results, an evaluation can be conducted on Sunarso, S.Sn (2.90) regarding his teaching performance. Keywords: Profile Matching, Decision Support System, Educator Performance                  Assessment, Web. Abstrak: Penilaian kinerja tenaga pendidik merupakan penilaian yang dilakukan melalui pengamatan dan pemantauan pada setiap butir tugas utama tenaga pendidik dalam rangka pembinaan karir, kepangkatan, dan jabatannya. Penilaian kinerja tenaga pendidik meliputi kemampuan tenaga pendidik dalam menguasai pengetahuan, keterampilan, dan sikap profesional sebagai pendidik. Untuk mengetahui kualitas SDM tenaga pendidik, salah satu upaya yang dapat dilakukan adalah dengan melakukan penilaian kinerja. Sebagai sebuah institusi pendidikan, kualitas SDM yang dimiliki sangat berdampak pada kualitas peserta didik. Tujuan penelitian ini  untuk menganalisa sebuah sistem pendukung keputusan dengan metode profile matching pada penilaian kinerja tenaga pendidik. Data yang di input ke dalam sistem ialah data kesesuaian pelaksanaan pembelajaran dengan jadwal pembelajaran, ketepatan waktu, penguasaan materi, dan lain-lain yang terkait pembelajaran. Dari hasil pengujian sistem yang dilakukan terdapat nilai perolehan Supriyati, S.Pd (4,25) predikat sangat sesuai, Siti Malihatun Nikmah, S.PD (3,70) predikat sesuai, Kusmini, S.Pd (3,60) predikat sesuai, Singgih Peranowo, S.Pd (3,20) predikat sesuai, Nursamsyiah, S.Pd (3,10) predikat sesuai, Sunarso, S.Sn (2,90) predikat tidak sesuai, dari hasil tersebut dapat dilakukan evaluasi terhadap  Sunarso, S.Sn (2,90) atas kinerja pengajaran. Kata kunci: Profile Matching, Sistem Pendukung Keputusan, Penilaian Kinerja Tenaga Pendidik, Web.